MHD flow and heat transfer of a Bingham fluid in an eccentric annulus with the Hall effect - Sayed-Ahmed, Mohamed E.; Attia, Hazem A. (Computer Assisted Methods in Engineering and Science, 2007)
The steady laminar flow and heat transfer of an incompressible, electrically conducting, non-Newtonian Bingham fluid in an eccentric annulus are studied in the presence of an external uniform magnetic field . The inner cylinder is subject to a constant heat flux while the outer cylinder is adiabatic and, the viscous and Joule dissipations are taken into consideration. The governing momentum and energy equations are solved numerically using the finite difference approximations. The velocity, the temperature, the volumetric flow rate and the average Nusselt number are computed for various values of the physical parameters.